Qualidade do sono, componentes da fragilidade e composição corporal de idosos da comunidade de Lavras - Minas Gerais - Lage, Flávia Fonseca (2021)
Elderly people may have changes in sleep pattern and greater risk for sleep disorders. There is evidence that sleep quality influences body composition and has been associated with frailty in this population. Therefore, the aim of the present study was to evaluate the association between sleep quality with components of the frailty phenotype and body composition of elderly people in the community of Lavras-MG. This is an observational and cross-sectional study, carried out with elderly people at the age of 60, or older, of both sexes. To assess sleep quality, the Pittsburgh Sleep Quality Index (PSQI) and the Epworth Sleepiness Scale were applied. The frailty components were assessed through self-report of involuntary weight loss, decreased HGS (Hand Grip Strength), self-reported fatigue by the Geriatric Depression Scale (GDS), gait speed (GS) and physical activity level by a questionnaire adapted from the IPAQ (International Physical Activity Questionnaire). Anthropometric measurements of body weight, height, calf circumference (CC) and waist circumference (WC) were performed, and body composition was assessed by bioelectrical impedance. The sample had a total of 141 participants, of which 116 (82%) were female and 25 (18%) were male. The mean age of participants was 69.5±6.4 years. The mean score of all participants on the PSQI was 6.02±3.44, 60% had poor sleep quality. The average score on the Epworth Sleepiness Scale was 6.88±4.30 points. The prevalence of frailty was 2% and 38% were classified as pre-frail. The following correlations were found between the studied variables and sleep quality: BMI (r=0.186, p=0.027), CC (r=0.171, p=0.043), WC (r=0.180, p=0.033), GS (r=0.168, p=0.046), fat mass (%) (r=0.222, p=0.008), fat mass (Kg) (0.212, p=0.012) and depressive symptoms (r=0.381, p=0.000). The logistic regression test showed a significant positive association between HGS and a negative association between fat mass and depressive symptoms on sleep quality. The present study showed a high prevalence of poor sleep quality in the elderly in this community, a decrease in frailty and significant correlations between sleep quality and the frailty components of physical disability and depressive symptoms.